Perancangan Almari Pakaian Bayi Serbaguna Melalui Brainstorming Dengan Ibu Rumah Tangga - Mochamad Rofieq (Jurnal Teknik Industri, 2012)
Goal of designing baby cupboard is to make easy for the young mother that have a baby. It designed for any needs, example as place of clothes, tools of bath and tools of drink (thermos, teapot, milk, bottle), and in order to them not difficultto prepare baby's drink in the night. The technics has made to develop alternative is brainstorming. It used with collecting some suggestion from young mother that have a baby, mother to be and susters are in the hospital. From the result with this brainstorming made a Morfology Chart that use to choose the best alternative to design the baby cupboard product.